2017
DOI: 10.1371/journal.pone.0187107
|View full text |Cite
|
Sign up to set email alerts
|

Healthy competition drives success in results-based aid: Lessons from the Salud Mesoamérica Initiative

Abstract: ObjectivesThe Salud Mesoamérica Initiative (SMI) is a three-operation strategy, and is a pioneer in the world of results-based aid (RBA) in terms of the success it has achieved in improving health system inputs following its initial operation. This success in meeting pre-defined targets is rare in the world of financial assistance for health. We investigated the influential aspects of SMI that could have contributed to its effectiveness in improving health systems, with the aim of providing international donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Success also indicated to be birthed from a healthy level of competition between siblings, cousins, friends, fellow colleagues and rivals both on an interpersonal and professional level. This is further supported by evidence from a research published in PloS One 2017 [ 30 ].…”
Section: Discussionsupporting
confidence: 60%
“…Success also indicated to be birthed from a healthy level of competition between siblings, cousins, friends, fellow colleagues and rivals both on an interpersonal and professional level. This is further supported by evidence from a research published in PloS One 2017 [ 30 ].…”
Section: Discussionsupporting
confidence: 60%
“…Several methods of financing can be usedin particular, results-based financing in a solid accounting framework, and a regional approach different from the traditional one followed, which consists of targeting each country alone. 32,43 Contributors CEB conceived the manuscript. CEB, and AHM provided overall guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our qualitative work in Chiapas showed that the RBA model created a culture of accountability, which was strengthened following the failure to meet targets during the first measurement round. With the improvement plan, accountability trickled down to the level of health workers, who developed the habit of routinely checking supplies and ensuring shortages were avoided [ 36 ]. Third, it is possible that we have some self-reporting bias in our survey.…”
Section: Discussionmentioning
confidence: 99%
“…The SMI methodology was previously published [ 35 , 36 ]. Briefly, the IDB worked with countries to select the poorest regions for the intervention.…”
Section: Methodsmentioning
confidence: 99%